On the Structure–Property Relationship of Semi‐Coherent FeCr2O4/Cr2O3 Spinel/Corundum Interfaces - Blas Pedro Uberuaga; Peter Hatton; Aaron A. Kohnert; Tiffany C. Kaspar (Advanced Materials Interfaces, 2025)
Abstract Oxide heterointerfaces are extremely common in both natural and artificial composite structures, including corroded structural materials. Often, key properties such as segregation and atomic transport are dictated by the structure of these interfaces. However, despite this critical link, very few heterointerfaces have been studied in any detail at the atomic scale. Here, one important oxide heterointerface is examined, between spinel and corundum, using the chemical system FeCr2O4/Cr2O3 as a representative and technologically important case. Using atomistic simulation techniques, it is found that the structure, particularly the local chemistry, of the interface depends on the crystal chemistry at the interface. This atomic and chemical structure further impacts important properties such as defect segregation and mass transport. It is found that defects can nucleate at some regions of these interfaces and migrate back and forth across the corundum layer, suggesting high atomic mobility that may be important for the evolution of spinel/corundum composite structures in extreme conditions.